Longitudinal study of lung function in pregnant women: Influence of parity and smoking (Clinics, 2017)
OBJECTIVES: To evaluate pulmonary function in the first and third trimesters of pregnancy and analyze the influence of parity and smoking on spirometry parameters. METHODS: This longitudinal prospective study included a cohort of 120 pregnant women. The inclusion criteria were as follows: singleton pregnancy, gestational age less than 13.86 weeks, and no preexisting maternal diseases. The exclusion criteria were as follows: change of address, abortion, and inadequate spirometry testing. ClinicalTrials.gov: NCT02807038. RESULTS: A decrease in values of forced vital capacity and forced expiratory volume were noted in the first second from the first to third trimester. In the first and third trimesters, multiparous women demonstrated lower absolute forced vital capacity and forced expiratory volume values in the first second compared with nulliparous women (p